PENCIPTAAN BRIDAL GOWN MUSLIM INSPIRASI DARI BURUNG KAKAKTUA - Antika, Defi Dwi; Russanti, Irma (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
The creation of a bridal gown is inseparable from inspiration, which is the prose of creative thinking. In this study, inspiration is drawn from the beauty of the cockatoo, an endemic Indonesian fauna. The double diamond method is used for the creation process, which includes the stages of discovery, define, develop, and deliver. The discovery stage involves the search for ideas from the inspiration of the cockatoo, while the define stage involves elaborating themes in a moodboard. The develop stage produces design concepts, including feather embroidery that realizes the inspiration. The deliver stage involves product testing, resulting in bridal gowns and men's suit sets. The bridal gown, inspired by the cockatoo, combines traditional elements with modern touches, while the men's suit sets highlight uniqueness in classic design. The overall work reflects the beauty of Indonesian nature and innovative elements in wedding fashion.